2002
DOI: 10.1152/ajpendo.00191.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of IGF-I and IGF-binding proteins within diaphragm muscle in modulating the effects of nandrolone

Abstract: Recent studies suggest that the anabolic effects of testosterone in muscle may be mediated, in part, by the insulin-like growth factor (IGF) system. The aim of this study was to examine the effects of nandrolone (NAN) on both IGF-I and IGF-binding proteins (IGFBPs) in the diaphragm muscle of 1-yr-old female rats. NAN (6.6 mg · kg−1 · day−1) was infused continuously for 17 days using a subcutaneous Silastic implant, whereas controls (CTL) received blank capsules. Muscle fibers were classified immunohistochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 56 publications
(69 reference statements)
6
61
1
1
Order By: Relevance
“…In contrast, IGF-IEa was constitutively expressed in proliferation and differentiated C2C12 cells and was stimulated by a single ramp stretch but was reduced by repeated cycle stretch (Cheema et al 2005). Recent studies have suggested that the anabolic effects of androgens in muscle may be mediated, in part, by local IGF-I (Lewis et al 2002). In rats, the administration of nandrolone produced significantly higher levels of muscle IGF-I compared with rats without nandrolone treatment (Lewis et al 2002).…”
Section: Insulin-like Growth Factor-imentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, IGF-IEa was constitutively expressed in proliferation and differentiated C2C12 cells and was stimulated by a single ramp stretch but was reduced by repeated cycle stretch (Cheema et al 2005). Recent studies have suggested that the anabolic effects of androgens in muscle may be mediated, in part, by local IGF-I (Lewis et al 2002). In rats, the administration of nandrolone produced significantly higher levels of muscle IGF-I compared with rats without nandrolone treatment (Lewis et al 2002).…”
Section: Insulin-like Growth Factor-imentioning
confidence: 99%
“…In recent years, it has become increasingly apparent that the autocrine/paracrine insulin-like growth factor (IGF) system within skeletal muscle plays an important role in myogenesis and maintenance of muscle fiber growth (Lewis et al 2002). IGF-I is ubiquitously expressed in skeletal muscle and appears to be important in both the proliferation and differentiation of skeletal muscle myoblasts (Florini et al 1996, Layne & Farmer 1999.…”
Section: Insulin-like Growth Factor-imentioning
confidence: 99%
See 1 more Smart Citation
“…Testosterone acts as an anabolic signal in muscle and appears to exert its effects by increasing levels of IGF-I mRNA (42,56,119), Akt, Akt phosphorylation, and protein synthesis in muscle (114). Testosterone may also negatively regulate myostatin, since elevated myostatin levels are observed after castration in androgen-responsive muscle (68).…”
Section: Integration Of Signaling Pathways To Modulate Ups Function Imentioning
confidence: 99%
“…In rat diaphragmatic muscle, a dosedependent increase in IGF-I mRNA expression occurred following exposure to androgen (Lewis et al 2002). When harvested bovine male satellite cells were treated with various androgen concentrations (using trenbolone), a dose-dependent increase in IGF-I mRNA expression occurred (Kamanga-Sollo et al 2004).…”
Section: Mechanisms Of Androgen Actionmentioning
confidence: 99%